(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Dolzarbligi. Currently, various methods are used to diagnose neurological, orthopedic and other syndromes in patients with Cerebral Palsy (CP). In order to objectify the state of the child’s movement abilities, the traditional neurological and orthopedic clinical examination is complemented by various assessment scales (spasticity scale, muscle strength, gross motor functions, etc.) [1,2,3]. Despite a certain level of subjectivity, these scales make it possible to form a general idea about the state of the child’s motor function, to assess the dynamics of its development against the background of rehabilitation measures. Instrumental diagnostic methods are limited to radiography of the osteoarticular apparatus, myography. Based on the results of the above examination methods, clinical conclusions are made and a decision is made to use one or another method of surgical or neuro-orthopedic treatment [3,4,5]. In the recent literature, the effectiveness and appropriateness of using various treatment methods are widely discussed - these are staged casts, orthopedic surgical interventions, selective fasciofibromyotomy, botulinum therapy in the movement rehabilitation of patients with BMF. Taking into account the targeted surgical intervention, a more objective assessment of the state of the child’s motor skills, the readiness of his main structures that ensure the formation of movement is offered. A common and inexpensive method for this purpose is ultrasound (UZT). Until now, ultrasound examination has not been widely used in the practice of rehabilitation of patients with BMF, because there are no uniform methodological approaches, the indications for its use have not been determined, and its objectivity has not been evaluated [6,7,8,9]